Quercetin relaxes rat tail main artery partly via a PKG‐mediated stimulation of KCa1.1 channels. (25th March 2013) - Iozzi, D.; Schubert, R.; Kalenchuk, V. U.; Neri, A.; Sgaragli, G.; Fusi, F.; Saponara, S.
Abstract Aim Protein kinases, activated by vasodilator substances, affect vascular function by regulating large conductance Ca2+‐activated K+ (KCa1.1) channels. Thus, the aim of the present investigation was to address the hypothesis that quercetin‐induced vasorelaxation is caused by a PKG‐mediated stimulation of KCa1.1 currents. Methods Single freshly isolated myocytes and endothelium‐denuded rings of the rat tail main artery were employed for electrophysiological and contractility measurements respectively. Results Quercetin relaxed vessels and increased KCa1.1 currents in a concentration‐dependent manner: both effects were antagonized by the specific KCa1.1 channel blocker iberiotoxin. Stimulation of KCa1.1 currents was fully reversible upon drug washout, markedly reduced by Rp‐8‐Br‐PET‐cGMPs, a PKG‐inhibitor, but not affected by catalase. Quercetin shifted by 34.3 mV the voltage dependence of KCa1.1 channel activation towards more negative membrane potentials without affecting its slope. Under conditions of tight functional coupling between sarcoplasmic reticulum Ca2+ release sites and KCa1.1 channels, quercetin decreased both the frequency and the amplitude of KCa1.1 transient currents in a ryanodine‐like manner. Conclusion The natural flavonoid quercetin relaxes the rat tail main artery partly via a PKG‐mediated stimulation of smooth muscle KCa1.1 channels.